Contestations of the Liberal International Order: From Liberal Multilateralism to Postnational Liberalism - Tanja A. Börzel; Michael Zürn (International Organization, 2021)
The 1990s saw a systemic shift from the liberal post–World War II international order of liberal multilateralism (LIO I) to a post–Cold War international order of postnational liberalism (LIO II). LIO II has not been only rule-based but has openly pursued a liberal social purpose with a significant amount of authority beyond the nation-state. While postnational liberal institutions helped increase overall well-being globally, they were criticized for using double standards and institutionalizing state inequality. We argue that these institutional features of the postnational LIO II led to legitimation problems, which explain both the current wave of contestations and the strategies chosen by different contestants. We develop our argument first by mapping the growing liberal intrusiveness of international institutions. Second, we demonstrate the increased level and variety of contestations in international security and international refugee law. We show that increased liberal intrusiveness has led to a variety of contestation strategies, the choice of which is affected by the preference of a contestant regarding postnational liberalism and its power within the contested institution.
doi:10.7910/DVN/WEYEUM
Keywords: 330; liberal international order; liberal multilateralism; postnational liberalism; contestation; United Nations Security Council; Responsibility to Protect; International Criminal Court; European Union; International Refugee Law; European migration crisis